The implementation of the 𝘊𝘖𝘝𝘐𝘋-19 𝘙𝘦𝘨𝘶𝘭𝘢𝘵𝘪𝘰𝘯𝘴 𝘢𝘯𝘥 𝘙𝘦𝘲𝘶𝘪𝘳𝘦𝘥 𝘝𝘢𝘤𝘤𝘪𝘯𝘢𝘵𝘪𝘰𝘯 𝘗𝘰𝘭𝘪𝘤𝘺: rural university students’ experiences - Mokone, Juliet Seapehi (University of the Free State, 2024)
As an immediate response to the COVID-19 pandemic, many universities in South Africa had to create COVID-19-specific policies. Many of these policies outlined the precautions that both students and staff had to follow to keep safe. This also entailed restricted access to university campuses and mandatory vaccination. To give background to this, students from rural-based university campuses, predominately come from disadvantaged backgrounds. Therefore, this study has attempted to understand the experiences of rural university students from one campus when a COVID-19-specific policy was implemented. Because of the disadvantaged nature of rural-based university students, it is essential to understand how the implementation of this policy affected them. Currently, there are limited studies that have attempted to understand the experiences of rural-based students, from a policy standpoint. Hence, this study aimed to explore students’ experiences with the implementation of the 𝘊𝘖𝘝𝘐𝘋-19 𝘙𝘦𝘨𝘶𝘭𝘢𝘵𝘪𝘰𝘯𝘴 𝘢𝘯𝘥 𝘙𝘦𝘲𝘶𝘪𝘳𝘦𝘥 𝘝𝘢𝘤𝘤𝘪𝘯𝘢𝘵𝘪𝘰𝘯 𝘗𝘰𝘭𝘪𝘤𝘺 on a rural University campus. Different studies have indicated that the pandemic did in fact widen the already existing inequalities between rural and urban-based universities. And across the world, different universities employed similar strategies in managing the spread of the virus and the main objective was to ensure the safety of students. Similarly, in countries like the United States of America, Nigeria and China students were removed from their university campuses and institutions enacted COVID-19-specific guidelines and policies to manage the spread of the virus on their university campuses. Of course, this came with some problems, for example, in a country like Nigeria, online learning and teaching presented some challenges. Therefore, with reference to realist social theory, this study has used the qualitative approach to collect data. Two data collection strategies have been used, which are focus group discussion and document analysis. Stratified purposive sampling was used to select participants from a rural university campus. In addition, data was analysed using thematic analysis and critical policy analysis. Results obtained from this study indicate that to a certain extend the implementation of the 𝘊𝘖𝘝𝘐𝘋-19 𝘙𝘦𝘨𝘶𝘭𝘢𝘵𝘪𝘰𝘯𝘴 𝘢𝘯𝘥 𝘙𝘦𝘲𝘶𝘪𝘳𝘦𝘥 𝘝𝘢𝘤𝘤𝘪𝘯𝘢𝘵𝘪𝘰𝘯 𝘗𝘰𝘭𝘪𝘤𝘺 did present students with some challenges. Students did not have the knowledge or the resources to learn successfully online, and they felt that the policy took their away their autonomy when it came to choosing whether or not to vaccinate. To add to this, policy analysis indicated that the policy was more specific when it came to employees but with regards to students, there were many omissions and silences. In brief, the institution did have an ethical moral obligation to keep its community safe however other less coercive alternatives should have been explored rather than mandating vaccinations.
Dissertation (M.Ed.(Education Policy Studies))--University of the Free State, 2024
Keywords: COVID-19; Vaccination policies; Rural universities; COVID-19 Regulations and Required Vaccination Policy